Simultaneous determination of the UV-filters benzyl salicylate, phenyl salicylate, octyl salicylate, homosalate, 3-(4-methylbenzylidene) camphor and 3-benzylidene camphor in human placental tissue by LC–MS/MS. Assessment of their in vitro endocrine activity - Jiménez-Díaz, Inmaculada; Molina-Molina, José Manuel; Zafra-Gómez, Alberto; Ballesteros, Oscar; Navalón, Alberto; Real-Domínguez, María Macarena; Sáenz, José Maria; Fernández, Mariana; Olea, Nicolás (Elsevier, 2013)
UV-filters are widely used in many personal care products and cosmetics. Recent studies indicate that some organic UV-filters can accumulate in biota and act as endocrine disruptors, but there are few studies on the occurrence and fate of these compounds in humans. In the present work, a new liquid chromatography-tandem mass spectrometry (LC-MS/MS) method to assess the presence of six UV-filters in current use (benzyl salicylate, phenyl salicylate, octyl salicylate, homosalate, 3-(4-methylbenzylidene) camphor, and 3-benzylidene camphor) in human placental tissue is proposed. Bisphenol A-d16 was used as surrogate for the determination of benzyl salicylate, phenyl salicylate, octyl salicylate and homosalate in negative mode and benzophenone-d10, was used as surrogate for the determination of 3-(4-methylbenzylidene) camphor and 3-benzylidene camphor in positive mode. The found limits of detection ranged from 0.4 to 0.6ngg(-1) and the limits of quantification ranged from 1.3 to 2.0ngg(-1), while variability was under 13.7%. Recovery rates for spiked samples ranged from 97% to 104%. Moreover, the interactions of these compounds with the human estrogen receptor alpha (hERα) and androgen receptor (hAR), using two in vitro bioassays based on reporter gene expression and cell proliferation assessment, were also investigated. All tested compounds, except benzyl salicylate and octyl salicylate, showed estrogenic activity in the E-Screen bioassay whereas only homosalate and 3-(4-methylbenzylidene) camphor were potent hAR antagonists.
Keywords: Cromatografía; E-Screen; Gene expression; LC–MS/MS; Placental tissue; UV-filters